The Overexpression of Insulin-Like Growth Factor-1 and Neurotrophin-3 Promote Functional Recovery and Alleviate Spasticity After Spinal Cord Injury - Talifu, Zuliyaer; Qin, Chuan; Xin, Zhang; Chen, Yixin; Liu, Jiayi; Dangol, Subarna; Ma, Xiaodong; Gong, Han; Pei, Zhisheng; Yu, Yan; Li, Jianjun; Du, Liangjie (Frontiers in Neuroscience, 2022)
Objective: To investigate the effects of the exogenous overexpression of nerve growth factor NT-3 and IGF-1 on the recovery of nerve function after spinal cord injury (SCI) and identify the potential mechanism involved. Methods: Sixty-four female SD rats were randomly divided into four groups: an SCI group, an AAV- RFP and AAV-GFP injection group, an AAV-IGF-1 and AAV-NT-3 injection group, and a Sham group. After grouping, the rats were subjected to a ten-week electrophysiological and behavioral evaluation to comprehensively evaluate the effects of the intervention on motor function, spasticity, mechanical pain, and thermal pain. Ten weeks later, samples were taken for immunofluorescence (IF) staining and Western blot (WB) detection, focusing on the expression of KCC2, 5-HT2A, and 5-HT2C receptors in motor neurons and the spinal cord. Results: Electrophysiological and behavioral data indicated that the AAV-IGF-1 and AAV-NT-3 group showed better recovery of motor function (P＜0.05 from D14 compared with AAV-RFP+AAV-GFP group; P＜0.05 from D42 compared with SCI group) and less spasticity(4 to 10 weeks, at 5 Hz all P＜0.05 compared with SCI group and AAV- RFP+AAV-GFP group) but with a trend for more pain sensitivity. Compared with the SCI group, the Vonfrey value result of AAV-IGF-1 and AAV-NT-3 group showed lower pain threshold (P＜0.05 at 4-8 weeks), and shorter thermal pain threshold (P＜0.05 at 8-10 weeks）. IF staining further suggested that compared with the SCI group, the overexpression of NT-3 and IGF-1 in the SCI-R+G group led to increased levels of KCC2(p<0.05), 5-HT2A(p<0.05), and 5-HT2C(p<0.001) in motor neurons. WB results showed that compared with the SCI group, the SCI-R+G group exhibited higher expression levels of CHAT(p<0.01), 5-HT2A(p<0.05), and 5-HT2C(p<0.05) proteins in the L2-L4 lumbar enlargement. Conclusion: Data analysis showed that the overexpression of NT-3 and IGF-1 may improve motor function after SCI and alleviate spasms in a rat model; however, these animals were more sensitive to mechanical pain and thermal pain. These behavioral changes may be related to increased numbers of KCC2, 5-HT2A, and 5-HT2C receptors in the spinal cord tissue. The results of this study may provide a new theoretical basis for the clinical treatment of spinal cord injury.